Somatotype and body composition based on playing position in Peruvian U-20 football players - Caso-Mauricio, J.; Miranda Flores, M. A.; Javier-Aliaga, D.; Calizaya-Milla, Y. E.; Saintila, J. (Journal of Human Sport & Exercise, 2025)
Background. Football, like other sports, necessitates the development of specific skills to achieve optimal performance. Furthermore, the roles of each player must be individually tailored, taking into account their physical composition and body structure. This underscores the importance of understanding the anthropometric and morpho structural characteristics of athletes. In this context, the aim of the present study was to describe these characteristics in a sample of U-20 youth soccer players, based on their playing positions on the field. Methods. This study employed a cross-sectional design. A non-probabilistic sample of 120 athletes, aged 17 to 20, was drawn from a professional soccer club in Lima, Peru. Twenty-three anthropometric variables were measured following the protocols of the International Society for the Advancement of Kineanthropometry (ISAK), using Kerr`s 5-component method for body composition and the Carter and Heath somatotype classification. Results. The Kerr anthropometric method demonstrated high accuracy in estimating body weight (R² = .956, p < .05), with good agreement as confirmed by the Bland-Altman analysis. Significant differences were observed in favour of goalkeepers in variables such as height, weight, skinfold thickness, thigh and calf circumferences, biacromial diameter, humerus and femur breadths, as well as arm and forearm circumferences, compared to defenders, midfielders, and forwards. However, defenders demonstrated significantly greater thorax and calf perimeters (p < .05). Significant differences were also observed in body composition indicators, as per Kerr`s method, including adipose tissue, muscle mass, bone mass, and skinfold thickness, with goalkeepers showing higher values (p < .05). All groups were classified as balanced mesomorphs. Conclusion. The results emphasize the importance of tailoring training and nutritional interventions to the specific morpho structural characteristics of soccer players, based on their playing position.